Pengembangan Media Pembelajaran Matematika Berbasis Aplikasi Android Pada Materi Bentuk Aljabar Untuk Meningkatkan Hasil Belajar Siswa SMP - Maria Operati Edy Jebatu; Juliana M. H. Nenohai; Damianus D. Samo (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2022)
Technology in education demands innovative and creative learning by utilizing android smartphones to improve student learning outcomes. Therefore, this study aims to develop and produce an android-based application on algebraic form material to improve student learning outcomes for grade VII students of SMP Negeri 8 Kupang that is valid, practical, and effective and to find out teacher and student responses to the application.The method used in this study is the Research and Development (R&D) research method and the model used for ADDIE development which consists of 5 stages, namely analysis, design, development, implementation andevaluation (evaluation). Data collection techniques used are interviews, questionnaires and learning outcomes tests. The data analysis technique used is qualitative data analysis and quantitative data analysis.The results showed that the Algebra Learning Application met the valid, practical and effective eligibility criteria and was able to improve student learning outcomes. The average total validity by material experts is 4.01, education practitioners are 4.23, and media experts are 4.66, with the "valid" category. The average total practicality of the teacher is 4.81 and that of the students in the small group is 4.2, while in the large group is 4.62 with the "practical" category. The percentage of mastery learning using learning media is 83.33% in the "effective" category. There was an increase in interest and completeness of student learning outcomes which initially increased from 40% to 83.33% so that the Algebra Learning application was very feasible to use. Keywords: Algebraic Forms, Android, Students Learning Outcomes, Learning Media